Substitusi Tepung Labu Kuning Terhadap Tingkat Pengembangan Dan Daya Terima Cake Labu Kuning - NURCAHYAWATI, Alfiah Dwi, Eni Setyowati, SE, M.Si, Rusdin Rauf, S.TP., M.P (2015)
Background : Indonesian great effort to reduce consumption of wheat flour is changing or substitute to another flour resources based on pumpkin. Pumpkin flour have contain high of pro vitamin A or β-carotene 180SI/100 gram of pumpkin to make our vision better and help maintain the body's tissues, so it can be expand a new food product such as cake. Purpose : This research aimed to understand the effect of changing wheat flour to another flour based on pumpkin as a substitution based material of cake development and consumer acceptance. Research Method: This research used complete random design with four different sampling ratio of pumpkin flour, which is 0%, 5%, 10%, 15%. Data were analyzed of cake development and consumer acceptance using statistic test method One Way Anova and continued with Duncan Multiple Range Test (DMRT) with 95% significant ratio. Result : The result showed that cake development was affected by the substitution of pumpkin flour. 0% and 5% ratio of pumpkin flour substitute have a great result and have a good cake development. Cake with 5% ratio of pumpkin flour substitute were the most preferred by consumers. Conclusion: There was effect of substitution wheat flour into pumpkin flour on consumer acceptance and the cake development depending on the pumpkin flour ratio. Suggestion :Based on the highest consumer acceptance of cake, suggested to subtitute 5% ratio of pumpkin flour in cake.